PENERAPAN METODE DISCOVERY LEARNING DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT - Citra Retna Wulan; Intan Nurjanah; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the curiosity of researchers towards the application of the Discovery Learning method in learning to write anecdotal text in class X students. From this background, a formulation of the problem can be drawn whether the application of the Discovery Learning method can improve the results of writing anecdotes in class X? This study was intended to determine the learning outcomes of writing anecdotes for grade X students whether grades could increase after being treated or not. The method in this study is a one-group pretest-posttest design experimental method. The sample used is class X students with a total of 26 students. Data collection techniques in the study used pretest and posttest which were analyzed through statistical analysis techniques. Researchers also used research instruments, namely the pre-test questions sheet and the post-test question sheet. From the results of research based on data processing, students' ability to write anecdotal texts obtained an average pretest test score of 55.38 and after applying the Discovery Learning method the posttest average score of 76.25. Then the value of writing an anecdotal text goes up by 20.87. Normality test results 0.202> 0.05, the results of the posttest and pretest were normally distributed. In conclusion, the use of Discovery Learning methods on students' ability to write anecdotal texts can be significantly improved.